POSSIBLE NONCOLLINEAR MAGNETIC STRUCTURES ON CAMNO3 AND LaMNO3 - Agus Purwanto (Jurnal Sains Materi Indonesia, 2006)
POSSIBLE NONCOLLINEAR MAGNETIC STRUCTURES ON CAMNO3 AND LaMNO3. CAMNO3 and LaMNO3 ceramics crystallize in the orthorhombic Pnma and monoclinic P1121/a space group, respectively. It has been reported that the ceramics order collinear antiferromagnetically below T=140K and 130K, respectively. The manganese magnetic atoms in CAMNO3 are located in the 4(b) site, while those in LaMnO3 are in 2(c) and 2(d). As the manganese atoms are neither located in the rotation axis or the mirror plane of the crystallographic symmetry, the noncollinear arrangements should not be excluded. This paper reports the derivation of the possible magnetic structures of CAMNO3 and LaMnO3. The derivation is based on the magnetic(Shubnikov) space group and the group theory. The result is that all of the possible models allow for three moment components in the noncollinear arrangements. The possible magnetic structures for CAMNO3 are noncollinear antiferromagnetic, noncollinear ferromagnetic in the a-direction, noncollinear ferromagnetic in the b-direction, noncollinear ferromagnetic in the c-direction. The possible magnetic structures for LaMnO3 are noncollinear ferromagnetic in the c-direction and in the ab-plane.